The role of IFIH1 gene rs1990760 and rs2111485 single-nucleotide polymorphisms in generalized vitiligo predisposition - ONAN, Duru (Turk J Med Sci, 2019)
BACKGROUND/AIM: Interferon-induced helicase (IFIH1) is a gene locus that has been recently defined as a candidate for susceptibility to generalized vitiligo (GV). The objectives of this study were to assess the association of IFIH1 gene, rs2111485, and rs1990760 single-nucleotide polymorphisms (SNP) with susceptibility to GV and the autoimmune diseases accompanying GV. MATERIALS AND METHODS: We prospectively studied GV patients and frequency-matched healthy controls by age and sex. The genotypes of the participants were determined for rs1990760 and rs2111485 SNPs of IFIH1. Dominant, recessive, and additive models were evaluated for each SNP adjusted for age and sex. RESULTS: The patients and their controls were observed to be in the Hardy–Weinberg equilibrium for SNP1 (2q24.2, rs1990760, IFIH1, T/C) and SNP2 (2q24.2, rs2111485, IFIH1, G/A), respectively (all P > 0.7). For SNP1, every T allel addition was significantly associated with 1.53 times protectiveness in terms of vitiligo risk (P = 0.033). As for SNP2, every G allel addition was associated with 1.42 times protectiveness, close to statistical significance (P = 0.100). Conclusions: We detected that for SNP1, each T allel and for SNP2, each G allel are protective in terms of vitiligo development. Hereby, we confirmed that IFIH1 gene locus has a role in GV susceptibility.